The Importance of Database Design and Normalization Process - Tülay Fenerci (Türk Kütüphaneciliği)
Database management systems are major tools which provide management of organizations’ operational data via computers. However their efficient usage depends on how well database tables are organized. When undesigned data is sto-red in the database there probably occur some problems such as data repeating and waste of storage space. In order to prevent such problems a normalization process is applied to tables.Normalization is a process of refining relations where relations are formed by gathering attributes. Hence problems such as repeating of data, dependency and combined relationships are solved with normalized base tables.Therefore database design is an important fact in efficiency of database management systems.